Multivariate protein landscape of host response in hospitalised patients with suspected infection in the emergency department - Pratik Sinha; Alexandra B. Spicer; Sivasubramanium Bhavani; Carlos López-Espina; Gregory L. Watson; Akhil Bhargava; Lee Schmalz; Shah Khan; Matthew D. Sims; Ashok V. Palagiri; Alon Dagan; Karthik V. Iyer; et al. (Nature Communications)
Abstract Suspected infection requiring hospitalisation has highly heterogenous presentation. Yet, variances in host response and its implications are largely unknown. In this multicentre cohort of 3802 individual patients presenting to the Emergency Department (ED) with suspected infection requiring hospitalisation, we apply uniform manifold approximation and projections and K-means clustering to 29 plasma proteins to identify biologically discrete host response clusters. In this work, we first describe two large clusters, called “Dysregulated” and “Undifferentiated”, with abnormal protein concentrations and adverse outcomes in the former. Through further clustering, we identify 4 sub-clusters in the Dysregulated cluster, each with discrete biological signatures, clinical correlates, and outcomes. Clusters 3 and 4 are characterised by renal impairment and viral infections respectively. Clusters 5 and 6 are associated with bacterial culture positivity, with the former consistent with an immunosuppressed signature and worse outcomes, and the latter with gram-negative bacteria, higher IL-6 and IL-8, and better outcomes despite higher vasopressor use. These clusters are a biologically driven approach to characterising acute suspected infection and may lead to more targeted therapeutics.